Use of Metabolomic Approaches in Analysis of Medicinal Plants and Phytopreparations (Review) - A. A. Orlova; J. Strugar; O. Yu. Shtark; V. A. Zhukov; V. G. Luzhanin; M. N. Povydysh (Разработка и регистрация лекарственных средств, 2021)
Introduction. The purpose of the analytical review is to summarize the data of modern scientific literature on the directions and possibilities of using the approaches of metabolomics in the analysis of medicinal plants, plant raw materials and herbal drugs.Text. Analysis of literature data showed that metabolomic approaches have great potential in the field of quality control of multicomponent phytopreparations and biologically active additives, detection of falsifications of rare and expensive plant materials, chemosystematics of medicinal plants, study of the mechanisms of action and toxicity of medicinal plants, etc.Conclusion. Metabolic analysis can become an effective analytical platform both for phytochemical research of plant raw materials and for regular activities to control the quality of plant material and phytopreparations.